Prevalence of distressed financing among elderly in a North Indian District - Pavan Pandey; Shivendra Kumar Singh; Uday Mohan (Indian Journal of Community and Family Medicine, 2016)
Background: In some instances health related out of pocket expenditure can be catastrophic thus compelling individuals to raise money through unusual means. Such a situation becomes unavoidable if, there are either too many illnesses or shortage of money. We carried out this study to assess the proportion of elderly who availed distressed financing while availing health care and whether or not they avoided any health care need due to shortage of money. Methods: This was a community-based cross-sectional study. The present study was conducted on a total of 404 elderly residing in both the urban and rural parts of Lucknow district. Participants were selected from the community using multistage random sampling. Data was collected with the help of a pretested questionnaire, it collected information related to health care utilization, health care financing and health care need deferred due to shortage of money. Results: Overall the children were the most common source for healthcare financing and 16.8 % study participants faced financial hardship while availing health care. Most common reason for seeking distressed financing was for buying medicine (58.8%). Conclusion: Use of distressed financing was not uncommon. Families need to be protected from catastrophic health expenditure through an effective social insurance to prevent financial hardship.